2015
DOI: 10.1089/acm.2014.0274
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as a Treatment Modality in Dermatology: A Systematic Review

Abstract: Acupuncture improves outcome measures in the treatment of dermatitis, chloasma, pruritus, urticaria, hyperhidrosis, and facial elasticity. Future studies should ideally be double-blinded and standardize the control intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…In conclusion, this systematic literature review did not find high quality data to judge the effect of acupuncture as single treatment (monotherapy) for atopic itch in a clinical setting and therefore no evidence-based recommendations can be made based on this review. This is in contrast with several other systemic reviews that have been published in recent years, some of which claimed to have found such studies and therefore included them into their reviews (Ma et al 2015;Yu et al 2015) and very recently (Shi et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, this systematic literature review did not find high quality data to judge the effect of acupuncture as single treatment (monotherapy) for atopic itch in a clinical setting and therefore no evidence-based recommendations can be made based on this review. This is in contrast with several other systemic reviews that have been published in recent years, some of which claimed to have found such studies and therefore included them into their reviews (Ma et al 2015;Yu et al 2015) and very recently (Shi et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For future studies they asked for clear standardizing of the control intervention, exemplified with placebo acupuncture as the control for the evaluation of the validity of acupuncture points and meridians, blinding of participants to treatment modalites and blinding of acupuncturists to the disease being treated to exclude psychological and procedural bias in an area already prone to subjectivity (Ma et al, 2015).…”
Section: Atopic Dermatitis and Itch In Traditional Chinese Medicinementioning
confidence: 99%
“…Acupuncture is a type of traditional Chinese medicine that has been used in China for more than 2500 years. It involves stimulation of specific points on the skin using needlepoints, pressure or heat [14,15]. Other therapies related to acupuncture include electroacupuncture where an electrical stimulus is applied to acupuncture needles; point application therapy where herbal medicine paste is applied to acupuncture points and bloodletting where a small amount of blood is released by puncturing a superficial blood vessel.19 In acupuncture, sterile, hair-fine needles are inserted into points and localised regions of the skin, subcutaneous and muscle tissue to initiate release of neurotransmitters, cytokines and growth factors to mediate pain, itch and for skin healing [16,17].…”
Section: Acupuncture In Dermatologymentioning
confidence: 99%
“…As another form of traditional Chinese medicine, acupuncture is useful in treating a variety of dermatologic disorders, human papillomavirus warts included. As the research work goes further and becomes more detailed, increased importance has been attached to the neuroimmuno-modulation role of acupuncture in pathogenesis of dermatological HPV infections (31). There was a case report about the long-term therapy of traditional Chinese acupuncture clearing away a giant HPV wart that an HIV infected patient developed when cryotherapy failed (32).…”
Section: Comparison Of Baofukang and Ifn-α2b Indicated Thatmentioning
confidence: 99%